The supreme emergency of war: a critique of Walzer. (February 2014) - Neu, Michael
This is a critique of the way in which Michael Walzer applies the concept of supreme emergencies in war. It aims to show that Walzer is mistaken in reserving this concept, as well as the associated notion of dirty hands, for situations in which political communities, in a desperate struggle for survival, cannot help but kill innocents intentionally, rather than merely with foresight. If moral agents have moral reasons to proceed in a way which will foreseeably result in innocent people being killed, they are already facing a supreme emergency; the killing does not need to be intentional in some narrower sense for that to be the case. This article stays agnostic on whether or not war can be morally justified in principle, and also on whether or not a dirty hands conception of war is ultimately defensible. It merely argues that if there are supreme emergencies as Walzer describes them, then situations in which war can justifiably be waged are, and ought to be, such emergencies.